Multistage progressive evolution of rare osumilite‐bearing assemblages preserved in ultrahigh‐temperature granulites from In Ouzzal (Hoggar, Algeria). (19th February 2013) - Adjerid, Z.; Godard, G.; Ouzegane, KH.; Kienast, J.‐R.
Abstract Osumilite is reported in Palaeoproterozoic Al–Mg‐rich granulites from the Khanfous area (Tekhamalt, In Ouzzal, Hoggar, Algeria). The main peak assemblages are osumilite + sapphirine + biotite + orthopyroxene + sillimanite and osumilite + orthopyroxene + sillimanite + quartz ± biotite (±K‐feldspar) in silica‐deficient and silica‐saturated granulites respectively. Osumilite coexists with F‐rich biotite (XF ≈ 0.6). The observed microstructures, the mass balance of metamorphic reactions and P–T pseudosections modelled for bulk‐rock and reaction‐microdomain compositions indicate a clockwise P–T metamorphic evolution at ultrahigh temperatures, without substantial post‐peak deformation. The peak P–T conditions recorded by the osumilite‐bearing assemblages are 8.5–9.0 kbar and 930–980 °C. During retrogression, osumilite was partially or totally replaced by fine‐grained pseudomorphs of cordierite + orthopyroxene + K‐feldspar + quartz at ~7 kbar and ~850 °C. This study confirms that osumilite can occur only in Mg‐rich metamorphic rocks that experienced ultrahigh‐temperature metamorphism under anhydrous conditions. In the presence of a hydrous fluid, it is replaced, even at high temperatures, by cordierite‐bearing assemblages. This important feature explains the rarity of osumilite in granulite facies rocks and its common replacement by cordierite + orthopyroxene + K‐feldspar + quartz pseudomorphs. The peak conditions suggest that a delamination of the lithospheric mantle underneath the In Ouzzal crust brought the asthenosphere close to the Mohorovičić discontinuity.